Assessment of Fall, Dependency, and Stroke Knowledge In CKD Patient With Comorbidities - Pebriana, Tika Rifa Luthfiyah; Kurniawan, Titis; Nursiswati, Nursiswati (Journal of Nursing Care, 2025)
Chronic kidney disease (CKD) is a global health problem that can lead to serious complications. In patients with CKD and diabetes mellitus (DM), there is an increased risk of falls, dependence in daily activities, and stroke. Although these risks are often associated with the elderly population, the phenomenon of multimorbidity is now also increasing trends among individuals of working age. This study aims to describe changes in fall risk levels, dependency levels, and stroke risk knowledge among CKD patients with DM and glaucoma during hospital care. Data collection was conducted through observation, interviews, physical examinations, and medical record reviews. The sample used was a 43 year old woman. The study results showed a significant improvement in reduced fall risk (MFS: 35 to 25), decreased dependency level (CDS: 53 to 66), and increased stroke risk knowledge (SRQ: 28 to 40). This study indicates that comprehensive interventions such as hemodialysis, wound care, pharmacological therapy, and education effectively improve functionality and understanding in productive aged patients with complex multimorbidity.